Indazoles: a new top seed structure in the search of efficient drugs against Trypanosoma cruzi. (October 2013) - Aguilera-Venegas, Benjamín; Olea-Azar, Claudio; Arán, Vicente J; Speisky, Hernán
For years, Chagas disease treatment has been limited to only two drugs of highly questionable and controversial use (Nifurtimox ® and Benznidazole ® ). In the search of effective drugs, many efforts have been made, but only a few structures have emerged as actual candidates. Heading into this, the multitarget-directed approach appears as the best choice. In this framework, indazoles were shown to be potent Trypanosoma cruzi growth inhibitors, being able to lead both the formation of reactive oxygen species and the inhibition of trypanothione reductase. Herein, we discuss the main structural factors that rule the anti- T. cruzi properties of indazoles, and how they would be involved in the biological properties as well as in the action mechanisms, attempting to make parallels between the old paradigms and current evidences in order to outline what could be the next steps to follow in regard to the future drug design for Chagas disease treatment.